Draft Annual Plan 1979-80(Supplementary Plan) Andaman and Nicobar Administration - Planning Commission (Planning Commission, 1979)
Little Andaman Island (282.4 sq. miles) was practically uninhabited till 1969 except by about 112 tribal people called "Onges". Too Island has been found, by Agricultural Experts, to be eminently suitable for reclamation and agricultural resettlement. Unlike other islands in the Andaman group, Little Andaman is also blessed with several perennial streams.
Andaman and Nicobar Administration, Rehabilitation Department